Desenvolvimento de um protótipo de fotômetro de chama portátil - Fernandes, Julys Pablo Atayde (2014)
Commercial flame photometers require a dedicated gas system and have considerable mass and volume, i. e., they are not portable. This work, as such, proposes the development of a portable flame photometer (prototype) using a torch lighter as the atomizer and controller, with an internal gas supply system, and managed by an Android mobile device. The internal control of prototype and the signal processing were performed by an Arduino Uno single-board microcontroller. The Android application was developed in App Inventor, an open source integrated development environment created and maintained by Massachusetts Institute of Technology. The nebulization was accomplished by ultrasonic cavitation in an adapted low power humidifier, which produces an aerosol sample which consists of very small radii droplets. The initiallyturbulent aerosol flow, needed to be damped before it reached the flame. Initial testswith calibration solutions of K+ resulted in a calibration curve validated using analysis of variance, the limits of detection and quantification were estimated. Optimizations still need to be made in the nebulization and aerosol transport system to improve theefficiency and to minimize inter-contamination of samples during the measurements.